Workshop Public Speaking: To Be A Powerful Public Speaker - Sy. Nurul Syobah; Lukman Nurhakim; Mazidatus Sa’adah; Meilita Aullia Putri; Mona Tindas Gustiana; Rini Lestari; Riswan Riswan; A. Rivai Beta (Lembaga Pengembangan Kinerja Dosen, 2025)
The workshop